Carvacrol is highly disruptive against coagulase-negative staphylococci in in vitro biofilms. (December 2017) - Gaio, Vânia; Lima, Cláudia Afonso; Oliveira, Fernando; França, Ângela; Cerca, Nuno
Aim: To evaluate the antimicrobial activity of carvacrol against stationary-phase planktonic and biofilm cells of coagulase-negative staphylococci and comparison to traditional antistaphylococcal antibiotics.Materials & methods: The antimicrobial effect of carvacrol and antibiotics against planktonic and biofilm cells were assessed through quantification of the number of culturable and/or viable cells. Confocal laser scanning microscopy was used to evaluate the effect of carvacrol on the biofilm structure.Results: A concentration of 4 mM of carvacrol demonstrated a potent antimicrobial effect, vastly superior than ciprofloxacin, rifampicin, gentamicin and vancomycin, both in planktonic and biofilm cells.Conclusion: Carvacrol is a potential antimicrobial agent, which applicability for the prevention and/or treatment of coagulase-negative staphylococci biofilm-associated infections is worthwhile investigating in more detail.